Yeast Mating as a Tool for Highly Effective Discovery and Engineering of Antibodies via Display Methodologies - Baek, Du San; Park, Seong Wook; Adams, Cynthia; Dimitrov, Dimiter S.; Kim, Yong Sung (Methods in Molecular Biology, 2022)
Yeast surface display (YSD) is a powerful methodology for discovery and engineering of antibodies, and the yeast mating has been used to overcome low transformation efficiency of yeast in antibody library generation. We developed an optimized method of yeast mating for generating a large, combinatorial antibody fragment library and heterodimeric protein library by cellular fusion between two haploid cells carrying different library each other. This method allows for increased diversity in screening of target-specific fragment antigen-binding (Fab) antibodies as well as in the development of heterodimeric Fc variants for bi-specific antibody generation and T-cell receptor (TCR). Here we describe the efficient isolation of human antibodies against the activated GTP-bound form of the oncogenic Ras mutant (KRasG12D-GTP) by sequential isolation of their heavy chains (HCs) followed by combination with light chains (LCs) via the yeast mating process. This strategy facilitates guided selection of the antigen-specific HC with either a fixed functional LC, which has cytosol penetrating ability, or an LC library to generate the Fab. It also allows for deeper exploration of a sequence space with fixed diversity, leading to a higher probability of successful isolation of human antibodies with high specificity and affinity.
Keywords: Antibodies; Guanosine Triphosphate; Humans; Immunoglobulin Fab Fragments; Peptide Library; Saccharomyces cerevisiae; Antibody library; Antibody screening; Guided selection; KRas; Yeast mating; Yeast surface display